2011
DOI: 10.1155/2011/870902
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Surgery—Myths and Realities in Developing Countries: Experience from Eastern Nepal

Abstract: B.P. Koirala Institute of Health Sciences, Dharan, Nepal, is the only tertiary care referral centre in the eastern region of Nepal. This paper discusses the author's experience of starting a plastic surgery unit in eastern Nepal regarding need and present status of plastic surgery care in Nepal. Methods. We analyzed the data of patients treated in Plastic surgery unit from July 2007 to February 2009. We did evaluation regarding type of patients, procedures, and their outcome. We also evaluated the limitations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…13,14 Thus, there has been a subsequent call for plastic and orthopedic surgeons from high-income countries to engage in soft tissue coverage procedure training for surgeons in LMICs. 7,15,16 The advent of ortho-plastic surgery and its subsequent success may represent a possible solution for addressing the surgical disease burden. 17,18 Training orthopedic surgeons in locations where plastic surgeons are not readily available may be an effective intervention for scaling patient access to soft tissue coverage procedures in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Thus, there has been a subsequent call for plastic and orthopedic surgeons from high-income countries to engage in soft tissue coverage procedure training for surgeons in LMICs. 7,15,16 The advent of ortho-plastic surgery and its subsequent success may represent a possible solution for addressing the surgical disease burden. 17,18 Training orthopedic surgeons in locations where plastic surgeons are not readily available may be an effective intervention for scaling patient access to soft tissue coverage procedures in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Eastern Nepal and Zambia found that only 0,1%–10% of plastic surgery procedure was done for a solely cosmetic purpose. [419] However, the studies did not further specify the type of procedure. This finding is in contrast with data from other developing nations such as Brazil and Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier medical reports showed that plastic surgery practices in developing countries were still focussing on the unmet-need for reconstructive purposes in severe trauma, advanced malignancies, burn contractures and congenital deformities cases. [34] However, research in International Studies found evidence for globalisation of aesthetic plastic surgery that caused its increasing demand in several other developing countries such as Brazil, Russia, India and China. The reasons behind this normalisation and cultural habituation were Western world's interest in the global market, which led to its higher than ever influences to third-world countries; booming capitalist economy; a new trend of hyper-consumerism; emerging beauty industry and pageants and the dominance of youth culture, which is focusing on achieving modernity.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge exchange and training courses conducted by HIC specialists who can teach local professionals is a suggested method to build surgical capacity. [ 8 10 ] Training local orthopaedic surgeons in locations where there is little surgical subspecialist care may be a solution to promote complex soft-tissue defect management in LMICs, [ 11 – 13 ] and the Surgical Management and Reconstructive Training (SMART) course is one such approach that teaches orthopaedic surgeons the principles of soft-tissue reconstruction and complex fracture management. [ 10 ] The curriculum emphasizes lower extremity soft-tissue coverage (flaps) that can be performed without microvascular surgery.…”
Section: Introductionmentioning
confidence: 99%